Efek Molaritas Aktivator (NaOH) pada Beton Geopolymer dengan Bahan Pengikat Limbah Fly Ash PLTU Lontar: Molarity Effect of Activator (NaOH) on Geopolymer Concrete with Fly Ash Waste Binding Material from PLTU Lontar - Bawono, Dapit; Muin, Resmi Bestari (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2023)
The average temperature of the earth's surface has increased by 0.74 ± 0.18°C over the past hundred years, caused by 65% carbon dioxide (CO2) emissions. Of the total CO2 emissions, around 6% come from the cement industry. Geopolymer concrete can be a solution to the problem because it does not use cement as a binder, but uses fly ash and activator materials. This activator material is to activate fly ash to become a binder. The aim of this study was to determine the effect of variations in the molarity of the NaOH activator on the workability, setting time, and compressive strength of geopolymer concrete. This study used fly ash from PLTU Lontar with a ratio of NaOH:NNa2SiO3 of 1:1.5, then the NaOH was varied with concentration levels of 5 Molar, 8 Molar, 11 Molar, and 14 Molar. From this research, it is known that the molarity level of the activator (NaOH) affects the workability (slump value), setting time, and compressive strength of concrete. The higher the molarity level of the activator (NaOH), the lower the workability of the concrete (the slump value decreases), the slower the setting time of the concrete, and the higher the compressive strength of the concrete. The most optimal variation is 14 Molar NaOH geopolymer with a slump value of 15 cm, initial setting time of 90 minutes, final setting time of 203 minutes, and compressive strength at 28 days of 54.60 MPa.